Steno-Stiffness Approach for Cardiovascular Disease Risk Assessment in Primary Prevention. Issue 3 (March 2019) - Tomiyama, Hirofumi; Ohkuma, Toshiaki; Ninomiya, Toshiharu; Mastumoto, Chisa; Kario, Kazuomi; Hoshide, Satoshi; Kita, Yoshikuni; Inoguchi, Toyoshi; Maeda, Yasutaka; Kohara, Katsuhiko; Tabara, Yasuharu; Nakamura, Motoyuki; et al.
Abstract : Supplemental Digital Content is available in the text.